2018
DOI: 10.1016/j.jesf.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Detraining effects of regular Tai Chi exercise on postural control ability in older women: A randomized controlled trial

Abstract: Background/ObjectiveThis study aimed to investigate the training and detraining effects of Tai Chi (TC) on postural control ability in single leg stance (SLS) by conducting a single-blind randomized controlled trial.MethodForty-eight older women were randomly divided into the TC, brisk walking (BW), and control(C) groups by using computer-generated program. The participants completed a 16-week intervention training and 8-week detraining program. Postural control ability in SLS was tested at the baseline, 16 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
(64 reference statements)
1
16
1
1
Order By: Relevance
“…For the other stance tasks, reference values for healthy adults in the literature are scarce. One study reported an ellipse area of 138 mm 2 for the single leg stance in a control group of older adults [64], whereas we found values of 878 mm 2 , 3860 mm 2 and 384 mm 3 in our study (averaged values per second: 29 mm 2 , 129 mm 2 and 13 mm 3 ). However, it is unclear if the values were indeed averaged in the cited study.…”
Section: Balance Performancecontrasting
confidence: 99%
“…For the other stance tasks, reference values for healthy adults in the literature are scarce. One study reported an ellipse area of 138 mm 2 for the single leg stance in a control group of older adults [64], whereas we found values of 878 mm 2 , 3860 mm 2 and 384 mm 3 in our study (averaged values per second: 29 mm 2 , 129 mm 2 and 13 mm 3 ). However, it is unclear if the values were indeed averaged in the cited study.…”
Section: Balance Performancecontrasting
confidence: 99%
“…Through our systematic review protocol, a total of nine studies were considered eligible for inclusion in this study. Four studies showed effects that seemed relatively robust against the effects of detraining [15,20,22,23]. Common among these four seems to be a specific focus on balance training, in the form of aquatic balance training [15], weight-bearing (as opposed to seated) exercise [22], and Tai Chi [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies showed effects that seemed relatively robust against the effects of detraining [15,20,22,23]. Common among these four seems to be a specific focus on balance training, in the form of aquatic balance training [15], weight-bearing (as opposed to seated) exercise [22], and Tai Chi [20,23]. However, programs that did not specifically target balance, or did so on low intensity, seem less effective after detraining (i.e., brisk walking, whole body vibration training, low-intensity balance training, seated or weight-bearing resistance training).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, en el estudio que realizaron Sun W et al 9 , identificaron que al comparar el Tai Chi contra realizar ejercicio (que consistía en caminar rápido), ambos mejoraban el control postural sobre una pierna. Por su parte, Mortazavi H et al 10 , emplearon el Tai Chi para reducir el riesgo de caídas y encontraron que hubo una diferencia significativa entre los grupos al final de la octava y décima semana de práctica (p < 0.001), esto se traduce en que, con el paso del tiempo, el Tai Chi redujo el riesgo de caídas.…”
Section: Síntomas Físicosunclassified